(untitled) (Jurnal Wahana Konseling, 2025)
Gender issues in multicultural counselling are receiving increasing attention in the field of guidance and counselling. In culturally diverse societies, the concept of gender is not only limited to the binary identity of male and female, but also encompasses a broader spectrum of identities. Differences in social norms, expectations and gender stereotypes across cultures can affect individuals’ psychological well-being, especially for those who face a mismatch between their gender identity and prevailing social norms. Counsellors therefore play an important role in creating a safe and inclusive environment and understanding the social and cultural dynamics that influence clients’ gender experiences. This research uses the literature review method, which aims to analyse theories, methods, and previous research findings related to gender issues in multicultural counselling. Through this method, the researcher was able to identify gaps in research, develop new concepts, and understand the implications of cultural diversity on counselling practice. The results showed that an in-depth understanding of cultural influences on gender roles is crucial in creating more inclusive and responsive guidance and counselling services. Multicultural counsellors should have an awareness of the social and cultural factors that shape gender identity, so as to avoid bias and support gender equality in counselling practice. With the right approach, multicultural counselling can be an effective tool in helping individuals face gender challenges and improve their psychological well-being amidst cultural diversity.